2007
DOI: 10.1073/pnas.0610312104
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the selection of glycosylated substrates by SCF Fbs1 ubiquitin ligase

Abstract: The ubiquitin ligase complex SCF(Fbs1), which contributes to the ubiquitination of glycoproteins, is involved in the endoplasmic reticulum-associated degradation pathway. In SCF ubiquitin ligases, a diverse array of F-box proteins confers substrate specificity. Fbs1/Fbx2, a member of the F-box protein family, recognizes high-mannose oligosaccharides. To elucidate the structural basis of SCF(Fbs1) function, we determined the crystal structures of the Skp1-Fbs1 complex and the sugar-binding domain (SBD) of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 33 publications
4
82
0
Order By: Relevance
“…Glycans-Previous studies have shown that FBXO2 and FBXO6 bind glycoproteins containing N-linked high mannose glycans (3,23,26,29,33,34). This raises the following important question.…”
Section: Divergent Binding Of High Mannosementioning
confidence: 99%
See 1 more Smart Citation
“…Glycans-Previous studies have shown that FBXO2 and FBXO6 bind glycoproteins containing N-linked high mannose glycans (3,23,26,29,33,34). This raises the following important question.…”
Section: Divergent Binding Of High Mannosementioning
confidence: 99%
“…1A) (23,33). Because of the high degree of amino acid identity among the G domains of the FBA family members (supplemental Fig.…”
Section: A Hydrophobic Pocket In the G Domain Is Necessary For Glycopmentioning
confidence: 99%
“…Fbx2 recognizes glycosylated proteins that are retrotranslocated from the ER into the cytosol and targets them for destruction (Yoshida et al 2002;Mizushima et al 2007). Finally, some ubiquitin ligases interact preferentially with substrates that are sumoylated (Perry et al 2008).…”
Section: Fbw7mentioning
confidence: 99%
“…F-box proteins are the specificity factors in SCF; they interact with Skp1 through the N-terminal ϳ40-residue F-box motif to recruit substrates through their variable C-terminal protein-protein interaction domains, including WD40 repeats (Fbxw subfamily), leucine-rich repeats (Fbxl subfamily), and other different or unknown domains (Fbxo subfamily) (15,16). Recently, a new subfamily within the Fbxo family that recognizes N-linked oligosaccharide, so-called Fbs, has been identified (10,17). The accumulated evidence suggests that the large number and rich diversity of F-box proteins not only allow the recruitment of numerous, diverse substrates but also position them optimally for the ubiquitination reaction, an important feature of the SCF E3s (13,14).…”
mentioning
confidence: 99%